The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1161/strokeaha.114.006661
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Intracerebral Hemorrhage During Rivaroxaban Treatment

Abstract: N ovel oral anticoagulants (NOACs) reduce incidence of stroke and intracerebral hemorrhage (ICH) in patients with nonvalvular atrial fibrillation.1 Several studies demonstrated hematoma expansion in patients with ICH occurring during warfarin therapy and poor clinical outcomes.2 However, information regarding hematoma size, its expansion, and functional and vital outcomes of patients with ICH occurring during NOAC treatment have been limited and remain largely unclear.Cerebral microbleeds (CMBs) are said to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 9 publications
6
64
1
2
Order By: Relevance
“…It is well known that plasma factor VII and complexes of tissue factor/factor VIIa are important initiators of the coagulation cascade, and thus suppression of factor VII by warfarin may lead to increased hemorrhage. 58, 59 We found that a significant number of ADHF patients who were not treated with anticoagulants showed increased INR on admission. Therefore, warfarin should be used carefully during the acute phase of heart failure, although ADHF patients are susceptible to thromboembolism through diuretic use and activated coagulation system.…”
Section: Role and Choice Of Anticoagulants In Heart Failurementioning
confidence: 85%
“…It is well known that plasma factor VII and complexes of tissue factor/factor VIIa are important initiators of the coagulation cascade, and thus suppression of factor VII by warfarin may lead to increased hemorrhage. 58, 59 We found that a significant number of ADHF patients who were not treated with anticoagulants showed increased INR on admission. Therefore, warfarin should be used carefully during the acute phase of heart failure, although ADHF patients are susceptible to thromboembolism through diuretic use and activated coagulation system.…”
Section: Role and Choice Of Anticoagulants In Heart Failurementioning
confidence: 85%
“…However, when compared with combined warfarin, the hematomas were smaller, had no expansion, and had favorable functional/survival outcomes. 14 In this context, the once-a-day dosage, the need for monitoring the INR, no inferiority to warfarin in treating the atrial fibrillation, and the decreased risk of bleeding in comparison to warfarin have made rivaroxaban an attractive alternative in patients who plan to use this anticoagulant.…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, multiple cerebral micro bleeds were detected more frequently in the rivaroxaban group than in the warfarin group. 14 These are important data that we take into account in the selection of the patient for the use of the drug. Even in a young patient, as in the case presented and without other risk factors for bleeding, the use of rivaroxaban can be a triggering factor for the intracranial bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Although experimental models show that dabigatran 9 and rivaroxaban 10 -unlike warfarindo not increase ICH volume unless given at supratherapeutic doses, few data are available on the clinical and radiologic characteristics of NOAC-ICH. A small study from Japan recently reported that in 5 patients with ICH associated with the NOAC rivaroxaban, the mean hematoma volume was smaller than in a comparison group of ICH associated with warfarin, 11 and that functional outcomes were better in the NOAC group.…”
mentioning
confidence: 99%